Kualitas Produk dan Harga Motor Beat terhadap Keputusan Pembelian Konsumen Dealer Honda Muara Bulian (Studi Kasus Masyarakat Perumnas Muara Bulian) - Damanik, Eva Setia Rini; Ningsih, Yulia Istia (Universitas Batanghari Jambi, 2024)
This study will describe respondent responses to product quality, price, and purchasing decisions. This study is quantitative research, using a questionnaire given to the sample. This research was conducted at a Honda dealer at the Muara Bulian National Housing community who bought the BEAT motorcycle in 2022. In Research, researchers took a sample of 66 people. Population in research entire society who bought a Motor Beat in 2022. The results of this research showed that the Muara Bulian National Housing Society stated good of the quality of the Motor Beat product. Society considered that the price of the Motor Beat Beingwas in the affordable category, and society considered that purchasing decision a Beat motorbike was appropriate, and product quality and price influenced the decision to purchase a Beat motorbike by 77.0%